Role of SOCS2 in the Regulation of Immune Response and Development of the Experimental Autoimmune Encephalomyelitis - Allysson Cramer; Bruno Cabral de Lima Oliveira; Paulo Gaio Leite; David Henrique Rodrigues; Fatima Brant; Lisia Esper; Pollyana Maria Oliveira Pimentel; Rafael Machado Rezende; Milene Alvarenga Rachid; Antonio Lucio Teixeira; Ana Maria Caetano Faria; Mauro Martins Teixeira; et al. (Mediators of Inflammation)
Multiple sclerosis (MS) is an inflammatory disease of the central nervous system (CNS). Experimental Autoimmune Encephalomyelitis (EAE) is the most widely used animal model for the study of MS. The Suppressor of Cytokine Signaling (SOCS) 2 protein plays a critical role in regulating the immune responses. The role of SOCS2 during EAE has not been explored. EAE was induced in WT and SOCS2-/- mice using myelin oligodendrocyte glycoprotein (MOG35-55) peptide. Brain and spinal cord were examined during the peak (day 14) and recovery phase (day 28) of the disease. SOCS2 was upregulated in the brain of WT mice at the peak and recovery phase of EAE. The development of the acute phase was slower in onset in SOCS2-/- mice and was associated with reduced number of Th1 (CD3+CD4+IFN-γ+) cells in the spinal cord and brain. However, while in WT mice, maximal clinical EAE score was followed by a progressive recovery; the SOCS2-/- mice were unable to recover from locomotor impairment that occurred during the acute phase. There was a prolonged inflammatory response (increased Th1 and decreased Th2 and T regulatory cells) in the late phase of EAE in the CNS of SOCS2-/- mice. Transplantation of bone marrow cells from SOCS2-/- into irradiated WT mice resulted in higher lethality at the early phase of EAE. Altogether, these results suggest that SOCS2 plays a dual role in the immune response during EAE. It is necessary for damage during the acute phase damage but plays a beneficial role in the recovery stage of the disease.